Analisis Pemberdayaan Masyarakat dalam Kegiatan Peternakan Inti Rakyat (PIR) Ditinjau dari Ekonomi Syari’ah pada Desa Mekar Mulya Kecamatan Sekampung Kabupaten Lampung Timur Tahun 2020 - cipto darsono; Hidawiy Syam, Rofiq (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2022)
In general, the results of the research that the author did on fattening cattle, it can be concluded that Mekarmulya Village, Sekampung District, East Lampung, that in empowering the community in community-based livestock activities (PIR), there are four stages, namely the awareness stage, the capacity building stage, the empowerment stage, the capacity building stage (development of capacity) and the ability to expand connections, relationships and synergies while maintaining the values of mutual interest and commitment to mutual success (networking). starting from providing insight or knowledge about the benefits of participating in fattening cattle and the process of fattening cattle. Provide training to the participants prior to the fattening of the cows. Giving freedom to the participants so that the participants do not only focus on fattening cattle, but can carry out daily work activities. Income from participating in the people's nucleus farming (PIR) program has certainly experienced a lot of changes, and in the economy it has certainly experienced good changes, that way the economic changes in the household have changed quite well and people who have participated in the people's nucleus farming (PIR) can become better in the economy. The interest of the participants in participating in the people's nucleus farming (PIR) also varies, of course, some feel that the income they get from working for the company is not sufficient for their daily needs, and some are looking for income after retiring from the company.